Prognostic utility of hybrid coronary computed tomography angiography and myocardial perfusion imaging in elderly patients with suspected coronary artery disease - Ajosenpää, Iina (My University, 2024)
Old age is a widely known independent risk factor for atherosclerotic coronary artery disease (CAD), and it is also associated with increased CAD-related mortality. CAD is often underdiagnosed and undertreated in elderly population, who might sometimes present with atypical symptoms or be asymptomatic. Furthermore, older patients tend to be more susceptible for complications from invasive treatment approaches. The prognostic utility of sequential hybrid- imaging strategy (coronary computed tomography angiography (CCTA) followed by positron emission tomography (PET) myocardial perfusion imaging in those with obstruction) in old age remains unclear. We explored the predictors of adverse outcome in patients who underwent hybrid CCTA-PET for evaluation of suspected coronary artery disease. Retrospectively we enrolled 1948 patients (43.8 % ≥ 65 years) referred for CCTA due to suspected CAD from 2008 through 2016. Patients with obstructive CAD by CCTA (n = 657) underwent 15O-water PET under adenosine stress. Mean age was 61.9 ± 9.9 years, 58.9 % were females. Elderly patients had more often obstructive CAD by CCTA, and ischemia by PET. During a mean follow-up of 6.8 years, the composite adverse outcome (all-cause death, myocardial infarction, or unstable angina) was higher in patients ≥ 65, versus those < 65 years. Ischemia by PET predicted events with a hazard ratio of 5.65 (95 % CI 2.35-13.57) in older patients, and 7.01 (95 % CI 3.08-15.94) in younger patients. The prognostic utility of hybrid CCTA-PET imaging approach for predicting adverse events at long-term follow-up was similar between patients ≥ 65 and those < 65 years.
Keywords: coronary artery disease, computed tomography angiography, positron emission tomography, elderly, prognosis